The Effect of Price, Product Variety and Customer Experience on Repurchase Intention Repurchase of Selsun Shampoo Products on the Shopee E-Commerce Platform - Talu, Sarlince; Widarta, Widarta (Formosa Journal of Applied Sciences, 2024)
Purposive random sampling was used to obtain 97 samples for the study. The research findings show that: 1. Price has no visible impact on the desire to repurchase Selsun shampoo products on the Shopee e-commerce platform; 2. Product Variety has no visible impact on the desire to repurchase Selsun shampoo products on the Shopee e-commerce platform; 3. Customer Experience significantly increases the desire to repurchase Selsun shampoo products on the Shopee e-commerce platform; and 4. Price, Product Variety, and Customer Experience significantly increase the desire to repurchase Selsun shampoo products on the Shopee e-commerce platform. Price, Product Variety, and Customer Experience together influence the desire to repurchase Selsun shampoo products on the Shopee e-commerce platform.